Tax Policy Issues Relevant to Captive Insurance Companies in Alberta - Mike Dolson (The School of Public Policy Publications, 2022)
Alberta recently enacted legislation that will permit the creation of captive insurance companies. This legislation will not come into force until Proclamation, which is unlikely to occur before detailed regulations are promulgated to address capital requirements, financial reporting standards, the lines of insurance business that captives may undertake, or the persons who may be insured. These critical regulatory items are the subject of a separate research paper on the captive insurance market published by the School of Public Policy.